Clinical and economic implications of using daratumubab with lenalidomide in the 1st and 2nd lines of therapy for multiple myeloma patients - О. I. Ivakhnenko; V. V. Ryazhenov; N. A. Falaleeva (Фармакоэкономика, 2024)
Objective: to assess clinical and economic implications of adding daratumumab (Dara) to the “lenalidomide + dexamethasone” (Rd) treatment program in early lines of therapy for patients with multiple myeloma (MM) ineligible for high-dose chemotherapy (HDCT) with subsequent autologous hematopoietic stem cell transplantation (autoHPSCT).Material and methods. Partitioned survival model was developed to compare overall survival in the treatment programs of MM patients in the 1st to 3rd lines of therapy. The following treatment options were included in the analysis: 1st line – Dara+Rd; 2nd line – “carfilzomib + lenalidomide” (K+Rd) or “ixazomib + lenalidomide” (Ixa+Rd) triplets; 3rd line – pomalidomide (Pom+dex) and Rd+(Dara+Rd)+(Pom+dex) versus Rd+(K/Ixa+Rd)+(Pom+dex/Dara). Probabilities of transition between health states (progression-free, progressed disease, and death) were based on published clinical data. Lifetime direct healthcare costs and incremental cost-effectiveness ratios (ICERs) per 1 life year gained were calculated from a Russian health care perspective. The indicator of the difference in costs between current and expected practice was used in budget impact analysis.Results. Dara+Rd combination increased life expectancy by 1.04 years (+16.05%) and 0.95 years (+14.57%) per patient, and in the target population (n=955) by 995.48 and 903.40 years for (Dara+Rd)+(K+Rd)+(Pom+dex) and (Dara+Rd)+(Ixa+Rd)+(Pom+dex) treatment programs, respectively, compared to Rd use in the 1st line. The ICER per 1 life year gained for Dara+Rd in 1st line therapy was 8.95 mln rubles for (Dara+Rd)+(K+Rd)+(Pom+dex) and 8.41 mln rubles for (Dara+Rd)+(Ixa+Rd)+(Pom+dex). It's lower than the median ICER of 13.64 million per 1 life year gained for antitumor drugs used to treat cancer of lymphatic and hematopoietic tissues (reference ICER). Dara+Rd triplet is used in 2nd line therapy after Rd, the number of life years gained in the target population due to greater efficacy is higher by 291.50 years compared with K+Rd and by 203.93 years compared with Ixa+Rd. The ICER per 1 life year gained for Dara+Rd is also lower than the ICER reference value: 9.25 mln rubles versus 13.64 mln rubles. The budget impact analysis showed that using Dara in early stages of MM therapy does not increase drug provision costs in the target population.Conclusion. The obtained results allowed to conclude that it is economically feasible to add Dara to the 1st and 2nd lines of therapy in lenalidomide treatment programs for MM patients who are not candidates for HDCT with autoHPSCT.